Protocol No. 16 to the European Convention on Human Rights. Objective: “not to die of success” - Bengoetxea Caballero, Joxerramon (Journal of the Basque Parliament, 2020)
This article presents Protocol 16 added to the European Convention for the Protection of Human Rights and Fundamental Freedoms. This protocol has introduced a sort of preliminary reference mechanism to the Strasburg system of Human Rights protection. High-range Courts from the Contracting Parties can suspend proceedings and refer to the European Court of Human Rights a request for an advisory opinion on a question of principle relating to the interpretation of the rights and freedoms of the Convention and its protocols. The article goes through the main traits of the European Convention and the European Court of Human Rights, and then describes the main issues involved in the new Protocol 16. The article also briefly analyses the only advisory opinion given by the Strasburg Court so far, and discusses the possible impact of this new instrument.